KAJIAN UNTUK APLIKASI KONSEP ECOPARK PADA TAMAN KOTA YANG BERUKURAN SEDANG DI DKI JAKARTA DITINJAU DARI ASPEK PENGELOLAAN SUMBER DAYA AIR - Petrus Nugro Rahardjo (Jurnal Teknologi Lingkungan, 2007)
Because of too many environmental problems have already beencontinuing in Jakarta, the local government of Province DKI Jakarta isintensively doing huge environmental programs in order to cope with theproblems. One of the programs is the application of concept “Ecopark”in managing all of the cityparks or gardens in Jakarta. A lot ofcitygardens in Jakarta have not correctly been managed by the concept,especially gardens which are classified into medium size park. Theaim of this specific program is to optimize the environmental functionof all gardens in the field of water resource management, such asincreasing the efficiency in water resource exploitation, conservation ofthe water resource by rain harvesting and using of treated domesticalwastewater. Content of the assessment in this paper focused on threecitygardens, i.e Cisanggiri, Kelapa Cengkir Barat and Gandaria VGarden. The conclusion said that all the three gardens have an excellentpotential to be developed by the concept Ecopark.